A new risk model to predict time to first treatment in chronic lymphocytic leukemia based on heavy chain immunoparesis and summated free light chain. (26th July 2019) - Tadmor, Tamar; Braester, Andrei; Najib, Dally; Aviv, Ariel; Herishanu, Yair; Yuklea, Mona; Shvidel, Lev; Rahimi‐Levene, Naomi; Ruchlemer, Rosa; Arad, Ariela; Fogl, Claudia; Henig, Clara; et al.
Abstract: Background: Chronic lymphocytic leukemia (CLL) is frequently accompanied by immune dysregulation. Aims: In this multicenter prospective study, we investigated whether heavy + light chains (HLC: IgGκ, IgGλ, IgAκ, IgAκ, IgMκ, IgMλ) and IgG subclasses (IgG1, IgG2, IgG3, and IgG4) could be used as novel prognostic markers of immunoparesis in 105 treatment‐naïve patients with CLL. Results: Heavy + light chains immunoparesis of ≥1, ≥2, and ≥3 isotypes was evident in 74 (70%), 58 (55%), and 36 (34%) patients, respectively. Severe HLC immunoparesis was identified in 40 (38%) patients. Of the IgG subclasses, IgG1 and IgG2 were most frequently suppressed, affecting 46 (44%) and 36 (34%) patients, respectively; 63 (60%) patients had low levels of at least one IgG subclass. In multivariate analysis, severe HLC immunoparesis (hazard ratio [HR]: 36.5; P = .010) and ΣFLC ≥ 70 mg/L (HR: 13.2; P = .004) were the only factors independently associated with time to first treatment (TTFT). A risk model including these variables identified patients with 0, 1, and 2 risk factors and significantly different TTFT ( P < .001). Patients with two factors represented an ultra‐high‐risk group with a median TTFT of only 1.3 months. Conclusion: The above findings demonstrate the potential for the use of HLC immunoparesis, together with sFLC measurements, as future prognostic biomarkers in CLL.